Factors determining first influenza vaccination among individuals with type 2 diabetes in the CONSTANCES cohort by age group (younger than 65 years or 65 and older) - Sylvain Paquet; Virginie Ringa; Henri Panjo; Jeanne Sassenou; Marie Zins; Laurent Rigal (Human Vaccines & Immunotherapeutics)
Vaccine coverage against influenza is suboptimal among people with diabetes. Our principal objective was to study and compare the factors related to a first influenza vaccination in individuals with type 2 diabetes according to age group (<65 years and ≥ 65 years) and then to compare the older age group with diabetes to the general population of that age. This is a descriptive cross-sectional study within the French Constances cohort. The study populations were composed of people with type 2 diabetes and individuals without diabetes 65 years and older. Our variable of interest was the first reimbursement for a vaccine against influenza over the period from 2009 to 2019. We identified 2540 cohort members with type 2 diabetes (<65 years n = 1583; ≥65 years n = 957). The population without diabetes (≥65 years) comprised 18,364 individuals. The factors related to the first influenza vaccination differed significantly between the persons with diabetes younger than 65 years and those aged at least 65 years: age (OR = 1.01/OR = 0.89—P-interaction<0.001), poor perceived health (OR = 1.24/OR = 0.79—P-interaction = 0.048), and indicators of diabetes treatment quality [at least 2 hbA1c assays/year (OR = 1.91/0 R = 0.90—P-interaction<0.001), and blood pressure < 140/90 (OR = 1.24/OR = 0.90—P-interaction = 0.059)]. The only factor related to first influenza vaccination significantly different between individuals aged at least 65 years with and without diabetes was age (OR = 0.83/OR = 1.05—P-interaction<0.001). This study shows that trials are now needed to test the effectiveness of age- and sex-specific messages to increase influenza vaccination coverage among people with diabetes.